ANALISIS KEMAMPUAN KONEKSI MATEMATIS BERDASARKAN NCTM (NATIONAL COUNCIL OF TEACHERS OF MATHEMATICS) SISWA SMK KELAS XI JURUSAN MULTIMEDIA PADA POKOK BAHASAN HUBUNGAN ANTAR GARIS - Andrechiana Supriyadi, Eko Wahyu; Suharto, Suharto; Hobri, Hobri (Department of Mathematics Education , University of Jember, 2017)
Abstract. This paper describes the students' mathematical connection ability on the matter of relationship between lines based on NCTM (National Council of Teachers of mathematics). The mathematical connection indicator used in this research is six. Mathematical connection aims to help the formation of student perceptions by viewing mathematics as an integrated part with the real world. The data collected in this study is the ability of students' mathematical connections on the material relationships between lines obtained from the test of the mathematical connection ability of six subjects. Of the six subjects categorized in in three groups, namely upper group students, middle group students, and lower group students. Through the interview obtained more in-depth information about students' mathematical connection ability to the relationship between lines. This research uses qualitative approach with descriptive research type. The results of the research have been done, the upper group students are able to understand five to six indicators of mathematical connection, the middle group students are able to understand the four indicators of mathematical connections, while the lower group students are only able to understand two to three indicators of mathematical connections. Thus, it can be concluded that the higher the level of mathematical ability of students the higher the ability of mathematical connections. Keywords: Mathematical connections, NCTM